Radioactive iodine in low- to intermediate-risk papillary thyroid cancer - Zhao, Hengqiang; Gong, Yiping (Frontiers in Endocrinology, 2022)
It remains controversial whether papillary thyroid cancer (PTC) patients with low- to intermediate-risk disease should receive radioactive iodine (RAI) after total thyroidectomy (TT). We aim to identify those who might benefit from RAI treatment in PTC patients with cervical nodal metastasis after TT. Patients were divided into TT and TT+RAI groups from the Surveillance, Epidemiology, and End Results (SEER) database (2004–2018). Overall survival (OS) and cancer-specific survival (CSS) were compared, and propensity score matching (PSM) was performed between groups. A total of 15,179 patients were enrolled, including 3,387 (22.3%) who underwent TT and 11,792 (77.7%) who received TT+RAI. The following characteristics were more likely to present in the TT+RAI group: multifocality, capsular extension, T3, N1b, and more metastatic cervical lymph nodes. RAI was associated with better OS in low- to intermediate-risk PTC patients in the multivariate Cox regression model. The subgroup analysis showed that RAI predicted better OS in patients ≥55 years, American Joint Committee on Cancer (AJCC) stage II, and capsular extension with a hazard ratio (HR) (95% CI) of 0.57 (0.45–0.72), 0.57 (0.45–0.72), and 0.68 (0.51–0.91), respectively. However, RAI failed to improve the prognoses of patients with age <55 years, AJCC stage I, PTC ≤1 cm, and capsular invasion. In the PSM cohort with 3,385 paired patients, TT+RAI treatment predicted better OS compared with TT alone. In addition, TT+RAI predicted better OS in patients with metastatic cervical lymph nodes ≥2, multifocality, extracapsular extension, and American Thyroid Association (ATA) intermediate risk. In conclusion, RAI was associated with better OS in low- to intermediate-risk PTC patients with age ≥55 years, multifocality, extrathyroidal extension, and ATA intermediate risk. However, the survival benefit from RAI may be limited in patients with AJCC stage I, PTC ≤1 cm, unifocality, capsular invasion, and ATA low-risk diseases; these patients even showed pathological cervical lymph node metastasis.